Universal API for managing multiple cloud platforms - Azim, Syeda NoorJaha; Islam, Tajul; Sufian, Abu (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.